A Canadian Multicentre Case-Control Study of Sporadic Escherichia coli 0157:H7 Infection - Donna Holton; Jeff Wilson; Andrea Ellis; David Haldane; Nicole April; Karen Grimsrud; Brent Friesen; John Spika (Canadian Journal of Infectious Diseases)
OBJECTIVE: To evaluate further risk factors for Escherichia coli 0157:H7 infection including consumer preferences related to the consumption of ground beef and the role of person-to-person transmission of this infection.